2022
DOI: 10.2196/31629
|View full text |Cite
|
Sign up to set email alerts
|

Medication Optimization Among People With Type 2 Diabetes Participating in a Continuous Glucose Monitoring–Driven Virtual Care Program: Prospective Study

Abstract: Background The Onduo virtual care program for people with type 2 diabetes (T2D) includes a mobile app, remote lifestyle coaching, connected devices, and telemedicine consultations with endocrinologists for medication management and prescription of real-time continuous glucose monitoring (RT-CGM) devices. In a previously described 4-month prospective study of this program, adults with T2D and baseline glycated hemoglobin (HbA1c) ≥8.0% to ≤12.0% experienced a mean HbA1c decrease of 1.6% with no signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In our study, use of anti‐hyperglycaemic medications with proven cardiovascular benefits increased by >2‐fold with CGM use, with a trend towards less sulphonylurea and DPP‐4 inhibitor use and more utilization of angiotensin converting enzyme inhibitors or angiotensin receptor blockers. Similar to our findings, other CGM‐based studies have shown increased utilization of anti‐hyperglycaemic medications, including greater use of GLP‐1 receptor agonists and less use of sulphonylurea or DPP‐4 inhibitors 34 . Furthermore, although glycaemic control is not the target of blood pressure or lipid‐lowering medications, more intensive behavioural change and/or prescription practices to lower overall cardiovascular risk (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, use of anti‐hyperglycaemic medications with proven cardiovascular benefits increased by >2‐fold with CGM use, with a trend towards less sulphonylurea and DPP‐4 inhibitor use and more utilization of angiotensin converting enzyme inhibitors or angiotensin receptor blockers. Similar to our findings, other CGM‐based studies have shown increased utilization of anti‐hyperglycaemic medications, including greater use of GLP‐1 receptor agonists and less use of sulphonylurea or DPP‐4 inhibitors 34 . Furthermore, although glycaemic control is not the target of blood pressure or lipid‐lowering medications, more intensive behavioural change and/or prescription practices to lower overall cardiovascular risk (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…The participants of this study received real-time continuous glucose monitoring (RT-CGM) devices. Using a phone application and the data gathered from the devices, a care team was able to provide education and advice on lifestyle modification tailored to the patients’ needs ( 32 ), while making necessary therapy adjustments according to the actual recommendations of the ADA ( 33 ). Type 2 diabetic patients with HbA1c levels ranging from 8-12% were selected for the purposes of the study.…”
Section: Telemedicine and Diabetes Carementioning
confidence: 99%